Bacterial Biofilm Material Properties Enable Removal and Transfer by Capillary Peeling. Issue 46 (8th October 2018) - Yan, Jing; Moreau, Alexis; Khodaparast, Sepideh; Perazzo, Antonio; Feng, Jie; Fei, Chenyi; Mao, Sheng; Mukherjee, Sampriti; Košmrlj, Andrej; Wingreen, Ned S.; Bassler, Bonnie L.; Stone, Howard A.
Abstract: Biofilms, surface‐attached communities of bacterial cells, are a concern in health and in industrial operations because of persistent infections, clogging of flows, and surface fouling. Extracellular matrices provide mechanical protection to biofilm‐dwelling cells as well as protection from chemical insults, including antibiotics. Understanding how biofilm material properties arise from constituent matrix components and how these properties change in different environments is crucial for designing biofilm removal strategies. Here, using rheological characterization and surface analyses of Vibrio cholerae biofilms, it is discovered how extracellular polysaccharides, proteins, and cells function together to define biofilm mechanical and interfacial properties. Using insight gained from our measurements, a facile capillary peeling technology is developed to remove biofilms from surfaces or to transfer intact biofilms from one surface to another. It is shown that the findings are applicable to other biofilm‐forming bacterial species and to multiple surfaces. Thus, the technology and the understanding that have been developed could potentially be employed to characterize and/or treat biofilm‐related infections and industrial biofouling problems. Abstract : Bacterial biofilms cause serious problems in health and in industrial operations. Using rheological characterization and surface analyses of Vibrio cholerae biofilms, it is discovered how extracellular polysaccharides, proteins, and cells function together to define biofilm mechanical and interfacial properties. A capillary peeling technology is developed to remove biofilms from surfaces or to transfer intact biofilms from one surface to another.